Penggunaan Kata Baku dan Tidak Baku di Kalangan Mahasiswa - Fatimah Azzahra Dalimunthe; Yafizham Yafizham (BADAN PENERBIT STIEPARI PRESS, 2024)
Language is an expression that contains the intention to convey something to other people. Something intended by the speaker can be understood and understood by the listener or interlocutor through the language expressed. Indonesian is a language of unity, which means it is a connecting language between tribes in Indonesia. As a unified language, it must have a clear structure using standard words so that it becomes a good and correct language and is easy to understand. Students are people who often interact with other people of different ethnicities. Therefore, students must have knowledge and understanding of standard words so that the communication process is not hampered. However, nowadays many students have low knowledge and understanding of standard words and are more interested in foreign words or slang words combined with Indonesian. Students as agents of change should use standard words in Indonesian so that our unified language can be maintained and preserved and its existence is not replaced by foreign languages.